2016
DOI: 10.1007/s10964-016-0489-z
|View full text |Cite
|
Sign up to set email alerts
|

Does Mindset Intervention Predict Students’ Daily Experience in Classrooms? A Comparison of Seventh and Ninth Graders’ Trajectories

Abstract: One's beliefs about whether ability is fixed or malleable-also known as fixed or growth mindset-can impact academic outcomes. This quasi-experimental study investigated effects of a six-week classroom intervention targeting growth mindset on students' daily quality of experience in science classrooms. Seventh grade (N = 370) and 9th grade (N = 356) students (50 % female, 61 % Hispanic) were randomly assigned by classroom to either a mindset intervention condition or content writing task condition. Students pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 49 publications
5
59
1
Order By: Relevance
“…Finally, although the intervention effect sizes in the present research were small in an absolute sense, their magnitude is consistent with those found in mindset intervention studies that have focused on academic outcomes (Blackwell et al, 2007;Schmidt, Shumow, & Kackar-Cam, 2017;Yeager, Walton, et al, 2016). Students' academic outcomes are often driven by recursive processes, where earlier success begets future success, which in turn begets even further future success, and so on.…”
Section: Limitations and Future Researchsupporting
confidence: 85%
“…Finally, although the intervention effect sizes in the present research were small in an absolute sense, their magnitude is consistent with those found in mindset intervention studies that have focused on academic outcomes (Blackwell et al, 2007;Schmidt, Shumow, & Kackar-Cam, 2017;Yeager, Walton, et al, 2016). Students' academic outcomes are often driven by recursive processes, where earlier success begets future success, which in turn begets even further future success, and so on.…”
Section: Limitations and Future Researchsupporting
confidence: 85%
“…ird, we assumed that the mindset training would increase motivation, as was the case in previous studies (e.g., [2,19,25]). According to Pintrich et al [47], task value is seen as an indicator for learners' motivation.…”
Section: 1mentioning
confidence: 96%
“…A similar pattern has been reported in previous research. For example, students Education Research International experienced strong declines in perceived skill across the school year, which were only partly buffered by a mindset training [25]. Fredericks and Eccles [55] argue that such downward trend occurs naturally as competitiveness and social comparisons at school become stronger over time.…”
Section: Training Effects On Beliefs and Motivationmentioning
confidence: 99%
See 2 more Smart Citations